Karl Marx's Writings on Alienation - Musto, Marcello. author. aut Link
XX, 164 p. 1 illus.
Keywords: The theory of alienation occupies a significant place in the work of Marx and has long been considered one of his main contributions to the critique of bourgeois society. Many authors who have written on this concept over the 20th century have erroneously based their interpretations on Marx’s early writings. In this anthology, by contrast, Marcello Musto has concentrated his selection on the most relevant pages of Marx’s later economic works, in which his thoughts on alienation were far more extensive and detailed than those of the early philosophical manuscripts. Additionally, the writings collated in this volume are unique in their presentation of not only Marx’s critique of capitalism, but also his description of communist society. This comprehensive rediscovery of Marx’s ideas on alienation provides an indispensable critical tool for both understanding the past and the critique of contemporary society. Marcello Musto is Professor of Sociology at York University, Toronto, Canada, and has published worldwide in more than twenty languages. Among his most recent edited books there are Marx’s Capital after 150 Years: Critique and Alternative to Capitalism (2019), and The Marx Revival: Key Concepts and New Interpretations (2020). He is the author of Another Marx: Early Manuscripts to the International (2018), and The Last Years of Karl Marx: An Intellectual Biography (2020).